GLP-1 and SGLT2 Therapies in Type 2 Diabetes Mellitus. Cutting-Edge Approaches to Advancing Diabetes Care - Parfianowicz, Agnieszka; Alicja Surma (Journal of Education, Health and Sport, 2025)
Type 2 diabetes mellitus (T2DM) is a multifactorial disease characterized by insulin resistance, beta-cell dysfunction, and chronic hyperglycemia. Despite the availability of conventional therapies, significant unmet needs persist in achieving optimal glycemic control and reducing long-term complications. GLP-1 receptor agonists (GLP-1 RAs) and SGLT2 inhibitors represent two novel classes of antidiabetic agents that have transformed the therapeutic landscape. This paper explores their mechanisms of action, clinical benefits, and potential synergistic effects, emphasizing their impact on cardiovascular and renal outcomes. Challenges and future directions for these agents in personalized diabetes care are also discussed.